The effects of perceived social support and psychological capital on attitudes towards professional psychological help-seeking among Chinese college students: The mediating role of psychological help-seeking stigma - Yingying Xie; Lihua Yao; ChengRui Ye (PLoS ONE, 2026)
Objective This study grounded in resource conservation theory, examines the association between perceived social support and psychological capital on college students’ attitudes toward seeking professional psychological help, with particular emphasis on the mediating role of stigma for seeking professional psychological help. The aim is to provide a reference framework for promoting mental health among college students. Method We employed a cross-sectional design, investigated perceived social support, psychological capital, stigma for seeking professional psychological help, and attitudes toward seeking professional psychological help among 3,012 Chinese college students. Result The results indicated that perceived social support, psychological capital, and attitudes toward seeking professional psychological help were negatively associated with the stigma for seeking professional psychological help. Perceived social support and psychological capital were directly and positively associated with attitudes toward seeking professional psychological help. Furthermore, the stigma for seeking professional psychological help was found to mediate the association between perceived social support and psychological capital on attitudes toward seeking professional psychological help ( β = 0.1 [0.059, 0.138], β = 0.248 [0.21, 0.29]). This mediation explained 16% and 39% of the total association. Conclusion This study highlights the association between perceived social support and psychological capital and attitudes toward seeking professional psychological help among college students, while also identifying mediating role of stigma for seeking professional psychological help. These findings provide empirical support for designing effective interventions to improve college students’ attitudes toward seeking professional psychological help.